The Relationship among Emotional Stability Personality Traits, Self-efficacy and Organizational Commitments of Managers and Subordinates in Nepalese Saving and Credit Cooperatives - Basnet, Dess Mardan; Shrestha, Rohit Kumar; Birla, Mahima; Aryal, Narayan Prasad (Sahayaatra सहयात्रा, 2024)
The Saving and Credit Cooperative is a member-owned financial institution. The primary goal is to mobilize funds to improve the members' and society's socioeconomic position to generate profit within the community and its members. We examined the relationship between emotional stability (neuroticism), affective commitment, normative commitment, and continuance commitment of managers of saving and credit cooperatives in Kathmandu District. Likewise, the study investigated managerial-level employees’ self-efficacy and affective commitment. The study found the differences in commitment levels of managerial-level ethnic groups of SACCOS. The study found differences in organizational commitment levels between managerial-level employees and subordinates of SACCOS. The study has used three standardized questionnaires: The mini-IPIP Scale, the General Perceived Self-efficacy Scale, and the Organizational Commitment Scale. A purposive sampling method was administered (N=826). The data was collected from 206 SACCOS in the Kathmandu District. The samples were 189 managers and 637 subordinates of SACCOS respectively. A descriptive analysis was performed as well as Spearman’s Rank Correlation Coefficient, the Mann-Whitney U Test, and the Kruskal-Wallis H test were used to carry out the statistical analysis of the data. Emotional stability personality trait was negatively correlated with affective commitment and however, continuance, & normative commitment were insignificant. The results showed the differences in organizational commitment between the managerial position and subordinates. The organizational commitment did not find differences in ethnic groups of SACCOS.